Impacts of Policy Instruments to Reduce Congestion and Emissions from Urban Transportation : The Case of São Paulo, Brazil - Anas, Alex; Timilsina, Govinda R. (2012)
This study examines impacts on net social benefits or economic welfare of alternative policy instruments for reducing traffic congestion and atmospheric emissions in São Paulo, Brazil. The study shows that expanding road networks, subsidizing public transit, and improving automobile fuel economy may not be as effective as suggested by economic theories because these policies could cause significant rebound effects. Although pricing instruments such as congestion tolls and fuel taxes would certainly reduce congestion and emissions, the optimal level of these instruments would steeply increase the monetary cost of travel per trip and are therefore politically difficult to implement. However, a noticeable finding is that even smaller tolls, which are more likely to be politically acceptable, have substantial benefits in terms of reducing congestion and emissions. Among the various policy instruments examined in the study, the most socially preferable policy option for São Paulo would be to introduce a mix of congestion toll and fuel taxes on automobiles and use the revenues to improve public transit systems.